Comparison of resazurin microtiter assay performance and BACTEC MGIT 960 in the susceptibility testing of Brazilian clinical isolates of Mycobacterium tuberculosis to four first-line drugs - Miyata, Marcelo [UNESP]; Pavan, Fernando Rogério [UNESP]; Sato, Daisy Nakamura [UNESP]; Marino, Leonardo Biancolino [UNESP]; Hirata, Mario Hiroyuki; Cardoso, Rosilene Fressati; Melo, Fernando Augusto Fiúza de; Leite, Clarice Queico Fujimura [UNESP] (Sociedade Brasileira de Microbiologia, 2013)
We assessed the performance of REMA in comparison with BACTEC MGIT 960 in the susceptibility testing of 80 Mycobacterium tuberculosis clinical isolates from Clemente Ferreira Institute against four drugs. REMA proved to be a rapid and accurate method, providing excellent correlation with BACTEC MGIT 960, with the exception of results for the ethambutol drug.
Keywords: Mycobacterium tuberculosis; tuberculosis; drug susceptibility testing